Percepção de professores e técnicos sobre o papel da escola na formação social de alunos em liberdade assistida no ensino médio - Corrêa, Alba Maria dos Anjos (2019)
This research is meant to investigate a current educational and social theme, discussing two points that are interconnected: the school history of students on probation in a public high school and why sometimes they refuse to acquire knowledge and do not interact with teachers and classmates. It seeks to comprehend the teachers and technicians’ knowledge of legislation and its influence on their practice. The research took place in a public High School in the city of São Paulo; it had been done through interviews with 6 teachers, 2 technicians from Núcleo Despertar do Amanhã and 1 social worker from CREAS. The intended objectives are investi-gating how teachers and technicians see these students on probation in public high schools, their professional experiences and their role on the formation of these students. The focus is in the schooling and in the school trajectory of students on probation. The study anchors itself on authors like Sácristan, Charlot, Esteve, Madeira e Mendonça, whose work are about students on probation, youth and school, familiar attendance, school and social relations, laws and laws infraction, school trajectory and education. As result of the research, teachers and technicians think that the school has a major role on the development of students on probation, however a educational system build to equalize all the students prevent the professionals of creating a specific method in behalf of these students, failing to attend their special needs